BLACK AND WHITE LAHAR AS INORGANIC SUPPORT FOR THE IMMOBILIZATION OF YEAST INVERTASE - Veronica C. Sabularse; Mayrene T. Tud; Marivic S. Lacsamana; Josefina L. Solivas (ASEAN Journal on Science and Technology for Development, 2005)
Volcanic ejecta or lahar can serve as an inorganic support for the immobilization of invertase. Pampanga and Bicol lahar samples were pretreated by ignition at 550oC for 5 hrs followed by concentrated hydrochloric acid treatment, activatedby reaction with aminopropyltriethoxysilane (APTS) and then covalently bound to invertase using glutaraldehyde as linker. Chemical tests confirmed the attachment of APTS to lahar and glutaraldehyde to silanized lahar. The quantity of immobilized invertase on Pampanga white, Pampanga black and Bicol black lahar were 98.73%, 96.73% and 84.27%,respectively. Conditions for maximum activity of invertase immobilized on Pampanga white lahar were pH 3.5, 45oC and 0.3 M sucrose concentration. The Kmand Vmaxfor free invertase and immobilized invertase on Pampanga white lahar were 2.37 M and 48.75 mmol/min, and 3.88 M and 38.87 mmol/min, respectively. Invertase bound to Pampanga white lahar was most stable towards repeated and continuous use and towards storage with intermittent use as indicated by its relatively greater activity.